2009
DOI: 10.1177/0146167208326477
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping Based on Voice in the Presence of Individuating Information: Vocal Femininity Affects Perceived Competence but Not Warmth

Abstract: about the category membership of stereotyped individuals (e.g., African American vs. White individuals) but also on physical cues or features that are associated with category membership but that concurrently vary within each category (e.g., Blair, Judd, & Chapleau, 2004;Blair, Judd, & Fallman, 2004;Blair, Judd, Sadler, & Jenkins, 2002;Eberhardt, Davies, Purdie-Vaughns, & Johnson, 2006;Livingston & Brewer, 2002;Maddox & Gray, 2002). So for instance, both Whites and African Americans who are clearly identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 51 publications
2
21
0
1
Order By: Relevance
“…For male job candidates, having a gay-sounding voice created a clear disadvantage when applying for a typically masculine, high-status position (Study 2a). Moreover, women with gender-atypical voices were discriminated when applying for a masculine job, despite the fact that masculinity is generally associated with greater leadership abilities (Schein, Mueller, Lituchy, & Liu, 1996), masculine lesbians are judged as more competent (Niedlich, Steffens, Krause, Settke, & Ebert, 2015), and masculine voice is associated with greater competence (Ko et al, 2009). Hence, heterosexism takes distinct forms for gay and lesbian individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For male job candidates, having a gay-sounding voice created a clear disadvantage when applying for a typically masculine, high-status position (Study 2a). Moreover, women with gender-atypical voices were discriminated when applying for a masculine job, despite the fact that masculinity is generally associated with greater leadership abilities (Schein, Mueller, Lituchy, & Liu, 1996), masculine lesbians are judged as more competent (Niedlich, Steffens, Krause, Settke, & Ebert, 2015), and masculine voice is associated with greater competence (Ko et al, 2009). Hence, heterosexism takes distinct forms for gay and lesbian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, are gay men stereotyped and discriminated because they sound gay or because they sound feminine? There is ample evidence that feminine sound (such as high pitch) is associated with reduced competence and leadership capacity both within and across gender groups (e.g., Klofstad et al, 2012; Ko et al, 2009) and that this occurs independently of sexual orientation. Similarly, our data suggest that gender-inverted inferences are common even among those participants who did not identify the speaker as gay or lesbian.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ko et al (2009) similarly reported that although job applicants with masculine voices were judged as being more competent, vocal masculinity/femininity did not predict judgments of warmth. Warmth entails “other-profitable” traits with immediate benefits to the assessor, as well as costs if it is misjudged (Fiske et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies with sighted listeners have indicated that speakers with low voice pitch are typically perceived as being more competent and trustworthy than speakers with higher voice pitch (Klofstad, Anderson, & Nowicki, 2015; McAleer, Todorov, & Belin, 2014; Tigue, Borak, O’Connor, Schandl, & Feinberg, 2012; Tsantani, Belin, Paterson, & McAleer, 2016). In contrast, studies examining voice-based assessments of warmth have produced equivocal results (Berry, 1991; Hughes, Pastizzo, & Gallup, 2008; Ko, Judd, & Stapel, 2009; McAleer et al, 2014). Recently, McAleer et al.…”
Section: Voice-based Assessments Of Social Traitsmentioning
confidence: 99%